Paraspinal Desmoid Tumor in a Pediatric Patient with No Surgical History: A Case Report - Patel, Aneek; Varga, Gregory; Mallela, Arka N.; Abou-Al-Shaar, Hussam; Bukowinski, Andrew; Mamauag, Erica; Zambrano, Eduardo V.; Greene, Stephanie (Asian Journal of Neurosurgery, 2024)
Desmoid tumors are locally aggressive, benign neoplasms originating in connective tissues. Although the exact pathophysiology remains unknown, antecedent trauma or surgery are believed to be important contributing factors. The occurrence of paraspinal desmoid tumor in pediatric patients is extremely uncommon. Here, we present an exceedingly rare case of a pediatric patient with no surgical or family history who developed a paraspinal desmoid tumor.A 9-year-old female patient presented with 4 months of progressive back pain, right lower extremity weakness, and numbness. Spinal imaging revealed a left epidural paraspinal mass compressing her thoracic spinal cord and extending into the left thoracic cavity. A multidisciplinary approach with neurosurgery and thoracic surgery enabled gross total resection of the lesion. The patient had complete resolution of her symptoms with no signs of residual tumor on postoperative imaging. Pathology revealed a desmoid tumor that avidly stained for beta-catenin. On her last follow-up, she developed a recurrence, to which she was started on sorafenib therapy.Desmoid tumors are rare connective tissue neoplasms that often occur after local tissue trauma, such as that caused by surgery. This report presents a rare case of a pediatric paraspinal desmoid tumor that occurred in a patient with no surgical or family history. Such tumors should undergo surgical resection for symptomatic relief and tissue diagnosis. Close clinical and radiographic surveillance are essential in these patients due to the high recurrence rates of desmoid tumor.
Keywords: desmoid tumor; epidural mass; wound healing; WNT pathway; beta-catenin; familial adenomatous polyposis; sorafenib